Microwave-assisted persulfate/peroxymonosulfate process for environmental remediation. (June 2022) - Bose, Saptarshi; Kumar, Mathava
Abstract : Sulfate radical (SO4 − ) generation from activated persulfate (PS) and peroxymonosulfate (PMS) processes has been receiving considerable attention in the field of environmental remediation. Because SO4 − has superior oxidation potential (E0 = 2.5–3.1 V) than other oxidants, non‐selective response to organic pollutants, wide operational pH range and longer life time (30–40 μs). Microwave (MW) irradiation (frequency from 0.3 to 300 GHz) has also gained a significant attention in environmental applications such as waste management and treatment including pyrolysis, water/wastewater treatment, phase separation and extraction processes, remediation of soil, hazardous and radioactive wastes and also in biomedical applications. The coupling of MW/PS processes is capable to generate high rate of sulfate radical as a result of the polar coupling, rapid and uniform heating, thermal and non‐thermal effects. Further, the addition of transitional metal-based catalysts and dielectric nonmetal catalysts in the MW/PS system was found to improve the oxidation efficiency of the system. In this review, the fundamentals and applications of MW activated persulfate/peroxymonosulfate (MW/PS or MW/PMS) process for environmental remediation of various systems including wastewater containing pharmaceuticals, different dyes, phenolic compounds, contaminated soil, and leachate treatment have been discussed. Moreover, the mechanism and recent developments in MW/PS and MW/PMS systems in the presence/absence of catalysts have been highlighted. Finally, a hybrid technical approach from futuristic development was addressed. Highlights: MW/PS or MW/PMS has better performance than MW-assisted hydrogen peroxide system. Rate of sulfate radical generation is higher from PS than PMS due to large O-O bond. SO4 − generated by thermal-decomposition, vibration and rotation of PS/PMS molecules. Dielectric and magnetic catalysts effectively increased the MW system performance. Hybrid MW/UV/PS/H2 O2 system can be energy efficient with lower residual SO4 .